(untitled) (Journal of actual problems of jurisprudence, 2020)
The article is devoted to the analysis of the development of the concept of a civil law contract. Although the doctrine of a civil contract has a long history of development, it is characterized by insufficient elaboration. Interest in this issue in legal science is still preserved. Initially, people received information about the institution of the treaty from myths, early religions, and ethical attitudes. The civil law contract is the subject of research of both domestic and foreign civil law and the general theory of law. Analysis of scientific, monographic, educational and methodological literature, legislation shows how ambiguous the views of researchers on the definition of the concept of “contract”. Particularly, the article emphasizes that a significant role in the development of contract law belongs to Roman lawyers. However, an analysis of the various types of contracts that existed in the Laws of 12 tables and in the Justiniаn Code allows us to conclude that Roman lawyers did not develop a unified understanding of the contract. The Roman treaty system distinguished two types of treaties: contracts and pacts. Studying and researching foreign civil legislation shows that the civil legislation of different states also has different formulations of the meaning of the concept of “agreement”. Key words: state, law, contract, legal system, legal institution, civil law, legal fact, legal relationship.